A comparative study of the moisture transfer properties and durability of PC and GGBS mortars - PAVIA, SARA (My University, 2007)
Ground Granulated Blast-furnace Slag (GGBS) is commonly used partially replacing Portland cement (PC) in concrete. GGBS is a finely-grained, basic slag with hydraulic properties and a high specific surface, produced as a by product in metallurgy. A number of authors have studied the influence of GGBS addition on the properties of OPC mortars and concrete concluding that GGBS enhances the general performance of PC composites improving workability, reducing creep and drying shrinkage, raising the ultimate compressive strength and reducing bleeding and heat of hydration. GGBS has been reported to improve the pore structure of PC decreasing salt diffusion thus incresing durability. However the most relevant hygric properties of GGBS mortar have not yet been studied. This paper provides an account of the most relevant hygric properties of GGBS and PC mortars. It compares the permeability, capillary suction, water absorption and compressive stregth of PC mortars incorporating GGBS in different proportions and studies how these properties vary as the mortars are subjected to artificial weathering in the laboratory. According to the results obtained, the PC mortars showed greatest permeability, water absorption and capillary suction and lower compressive strengths than the GGBS mortars. The PC mortars also showed the greatest rise in permeability, water absorption, capillary suction and mass loss as well as the greatest decrease in compressive strength as a result of weathering. According to these results, the addition of GGBS to OPC composites lowers the water absorption, capillary suction and permeability simultaneously increasing ultimate compressive strength and durability. This may be due to both the geometric characteristics and reactivity of the GGBS that allow a greater density and lower permeability due to the tight packing of the mortar?s microfabric as well as the presence of abundant early hydraulic cements.
International Conference on Concrete Platform
PUBLISHED
Keywords: capillary suction; compressive strength; durability; Ground Granulated Blast-furnace Slag GGBS; OPC; permeability; water absorption